2007
DOI: 10.1002/fld.1674
|View full text |Cite
|
Sign up to set email alerts
|

A well‐balanced Runge–Kutta discontinuous Galerkin method for the shallow‐water equations with flooding and drying

Abstract: SUMMARYWe build and analyze a Runge-Kutta Discontinuous Galerkin method to approximate the one-and two-dimensional Shallow-Water Equations. We introduce a flux modification technique to derive a wellbalanced scheme preserving steady-states at rest with variable bathymetry and a slope modification technique to deal satisfactorily with flooding and drying. Numerical results illustrating the performance of the proposed scheme are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
110
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 39 publications
6
110
0
Order By: Relevance
“…However, this Riemann solver is an ideal choice to be employed within RKDG methods for simulating shallow water flows when the model merely considers frictionless and horizontal channel flows [36]. The two articles of Ambati and Bokhove [51,52] are among the very few papers that deal with DG methods over dry beds [53,54]. In their work, the authors presented a second-order DG space-time FE discretization combined with an improvement to the HLLC [4] flux.…”
Section: Introductionmentioning
confidence: 97%
“…However, this Riemann solver is an ideal choice to be employed within RKDG methods for simulating shallow water flows when the model merely considers frictionless and horizontal channel flows [36]. The two articles of Ambati and Bokhove [51,52] are among the very few papers that deal with DG methods over dry beds [53,54]. In their work, the authors presented a second-order DG space-time FE discretization combined with an improvement to the HLLC [4] flux.…”
Section: Introductionmentioning
confidence: 97%
“…A recent review is performed in [80] and a unified analysis can be found in [3], and [26,27], respectively for elliptic problems and both 1 st and 2 nd order problems in the framework of Friedrichs' systems. The application of dG methods to the Saint-Venant equations (also called Nonlinear Shallow Water equations, NSW in the following) has recently lead to several improvements, see for instance [2,28,78,79] and the recent review [19]. However, dG methods for BT equations have been under-investigated.…”
mentioning
confidence: 99%
“…The success of Godunov-type flood models can be attributed to approximate Riemann solvers [37,75] which are also embedded in discontinuous Galerkin finite element schemes [4,26,45] and Boussinesq models that account for non-hydrostatic flow effects [47]. Godunov-type models have generally assumed either a structured mesh of quadrilateral cells [3,13,29,35,42,86] or an unstructured mesh of triangular cells [7,15,41,70,84].…”
Section: Introductionmentioning
confidence: 99%